1995
DOI: 10.1128/aac.39.1.107
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide sequence of the gyrA gene and characterization of ciprofloxacin-resistant mutants of Helicobacter pylori

Abstract: PCR was used to amplify a 238-bp region from Helicobacter pylori which corresponded to the quinolone resistance-determining region in Escherichia coli. The gyrA gene of H. pylori was cloned and sequenced. An open reading frame of 2,478 nucleotides coded for a polypeptide of 826 amino acids with a calculated molecular mass of 92,508 Da. The amino acid sequence showed an overall 52% identity with other bacterial gyrA genes but was most closely related to the gyrA subunit of Campylobacter jejuni (76.5% identity).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
116
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(125 citation statements)
references
References 36 publications
8
116
0
1
Order By: Relevance
“…mutations in the 23S rRNA, gyrA, rpoB and rdxA genes are associated with CLR, CIP, RIF and MTZ resistance respectively. [25][26][27][28][29][30] Nevertheless, the authors believe that the CLR/MTZ-based triple therapy is still effective as a first-line treatment, at least within Australia. Female patients are more likely to carry H. pylori strains resistant to both CLR and MTZ than male patients due to the higher incidence of previous treatment of gynaecological conditions with antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…mutations in the 23S rRNA, gyrA, rpoB and rdxA genes are associated with CLR, CIP, RIF and MTZ resistance respectively. [25][26][27][28][29][30] Nevertheless, the authors believe that the CLR/MTZ-based triple therapy is still effective as a first-line treatment, at least within Australia. Female patients are more likely to carry H. pylori strains resistant to both CLR and MTZ than male patients due to the higher incidence of previous treatment of gynaecological conditions with antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…Considering these facts, we believe that levofloxacin should be considered as one of the antibiotics used for second-or third-line H. pylori eradication therapy in children. Moore et al (1995) reported four mutations of the A subunit of the DNA gyrase (GyrA) at amino acid 87 (Asn to Lys), 88 (Ala to Val), 91 (Asp to Gly, Asn or Tyr) and a double substitution at 91 and 97 (Ala to Val) in H. pylori strains with secondary resistance to ciprofloxacin. Moreover, in one in vitro study with the serial passage method, GyrA mutation at amino acid 91 (Asp to Ala, Gly, Asn or Tyr) was also reported in the ciprofloxacin-resistant strains (Wang et al, 2001).…”
Section: S Fujimura and Othersmentioning
confidence: 99%
“…This enzyme contains two A subunits and two B subunits, encoded by gyrA and gyrB, respectively [11]. Resistance to fluoroquinolones is mainly mediated by a mutation in the Quinolone Resistance Determining Region (QRDR) in the gyrA gene [12].…”
Section: Open Accessmentioning
confidence: 99%